Intakhab-e-Zindagi : Ek Mukalma - Toynbee, Arnold ; Ikeda, Daisaku and Gage, Richard L.; Translated by Manzoor Ahmad (Lahore Peace Publications, 2018)
Interviews on issues confronting the contemporary human race, recorded and edited by Gage, with the text then revised and approved by Toynbee.
Keywords: Civilization, Modern--Philosophy -- Philosophical anthropology -- Communication in the humanities